2019
DOI: 10.1080/01402382.2019.1577069
|View full text |Cite
|
Sign up to set email alerts
|

Adult roles and the gender gap in political knowledge: a comparative study

Abstract: The unusual size and persistence of the gender gap in political knowledge is perplexing in comparison to other dimensions of politics. Building on situational explanations of political engagement, this article claims that women's and men's specific adult roles lead to an enlargement of the gender gap in knowledge. The present study analyses men and women's levels of political knowledge at different life stages by means of two unique datasets specifically collected to measure what people know about politics. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
(60 reference statements)
1
7
0
6
Order By: Relevance
“…In contrast, following the birth of a child, men lessen their dedication to household work and increase the hours in the workplace to maximize economic rewards (Bianchi et al, ; Burns et al, ). Scholars have shown that marriage and especially parenthood is detrimental to European women's social networking and political knowledge and engagement, but not that of men (Ferrin, Fraile, & García‐Albacete, ; García‐Albacete, ; Quaranta & Dotti Sani, ). As a result, women are less likely than men to benefit from the economic and cognitive resources provided by the working environment, which enhance political learning and engagement (Burns et al, ).…”
Section: Sex Role Socialization and Political Engagementmentioning
confidence: 99%
“…In contrast, following the birth of a child, men lessen their dedication to household work and increase the hours in the workplace to maximize economic rewards (Bianchi et al, ; Burns et al, ). Scholars have shown that marriage and especially parenthood is detrimental to European women's social networking and political knowledge and engagement, but not that of men (Ferrin, Fraile, & García‐Albacete, ; García‐Albacete, ; Quaranta & Dotti Sani, ). As a result, women are less likely than men to benefit from the economic and cognitive resources provided by the working environment, which enhance political learning and engagement (Burns et al, ).…”
Section: Sex Role Socialization and Political Engagementmentioning
confidence: 99%
“…We included various socio‐demographic characteristics as independent variables. Given the literature on the gender gap in political knowledge (Dassonneville & McAllister, ; Ferrín, Fraile, & García‐Albacete, ; Pereira, ), we expect men to answer more questions correctly than women. Similarly, older respondents may have had a higher chance to get into contact with the welfare state or research on social policy and may thus perform better.…”
Section: Predicting Policy Knowledgementioning
confidence: 99%
“…El conocimiento político, el rango de información sobre hechos y eventos políticos, es un recurso indispensable para la eficaz ejecución de las responsabilidades de un ciudadano, su empoderamiento y el desarrollo socioeconómico de una sociedad (Delli & Keeter, 1996). Las personas con un grado más alto de sofisticación política tienen mayor capacidad para alinear conscientemente sus opiniones con la elección de sus representantes y sus opiniones son menos fluctuantes a lo largo del tiempo, o son víctimas de información oportunista (Dassonneville & McAllister, 2018;Ferrín et al, 2019;Luskin, 1990;Wolak & McDevitt, 2011). Igualmente, la carencia de información política relevante está relacionada con la inhabilidad para influir en el proceso político y traducir el apoyo político a un candidato en beneficios concretos para el individuo y su comunidad (Fraile & Gómez, 2015;García, 2015), tal como presentar denuncias, conocer los derechos de los cuales goza, requerir ayuda de la institución adecuada, entre otros.…”
Section: Información Política Y Brecha De Génerounclassified
“…ej., "la política es cosa de hombres") (Delli & Keeter, 1996;Dolan, 2011;Dow, 2009), las hace más aversivas al riesgo (p. ej., responden "no sé" o no responden si no están completamente seguras de tener una respuesta correcta) (Lizotte & Sidman, 2009;Mondak & Creel, 2001;Mondak & Anderson, 2004) y socialmente las confina al ámbito familiar y las desalienta de participar en el ámbito público (Ferrín et al, 2019;Fox & Lawless, 2004). Otro aspecto que se ha sido estimado influyente en las últimas dos décadas es la adquisición de información por las redes sociales (Bode, 2016;Cacciatore et al, 2018;Gil de Zúñiga et al, 2017;Prior, 2005).…”
Section: Información Política Y Brecha De Génerounclassified
See 1 more Smart Citation